BigMouth: a multi-institutional dental data repository. (3rd July 2014) - Walji, Muhammad F; Kalenderian, Elsbeth; Stark, Paul C; White, Joel M; Kookal, Krishna K; Phan, Dat; Tran, Duong; Bernstam, Elmer V; Ramoni, Rachel
Abstract: Few oral health databases are available for research and the advancement of evidence-based dentistry. In this work we developed a centralized data repository derived from electronic health records (EHRs) at four dental schools participating in the Consortium of Oral Health Research and Informatics. A multi-stakeholder committee developed a data governance framework that encouraged data sharing while allowing control of contributed data. We adopted the i2b2 data warehousing platform and mapped data from each institution to a common reference terminology. We realized that dental EHRs urgently need to adopt common terminologies. While all used the same treatment code set, only three of the four sites used a common diagnostic terminology, and there were wide discrepancies in how medical and dental histories were documented. BigMouth was successfully launched in August 2012 with data on 1.1 million patients, and made available to users at the contributing institutions.